Efektivitas Pemberian Edukasi Metode Ceramah dan Demonstrasi terhadap Pemahaman dalam Penggunaan Birth Ball pada Ibu Hamil di TPMB N Kabupaten Malang - Cut Afni Zhahara; Tavip D.W.; Naimah Naimah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pregnancy is frequently associated with discomforts such as back pain, edema, and postural changes that may interfere with daily activities. Approximately 50–70% of pregnant women experience back pain due to hormonal changes and increased body weight. The use of a Birth Ball is considered one of the non-pharmacological alternatives to alleviate these complaints, as it improves pelvic muscle flexibility and supports postural correction. Proper education is essential to ensure appropriate and effective utilization. This study aimed to evaluate the effectiveness of education using lecture and demonstration methods on the understanding of Birth Ball use among pregnant women. A pre-experimental design with a one-group pre-test post-test approach was applied. The sample consisted of 28 third-trimester pregnant women selected through purposive sampling. Findings revealed that the respondents’ understanding prior to education was 0%, which significantly increased to 96.43% following the intervention. Statistical analysis using the Wilcoxon Signed Rank Test yielded Z = -4.873 with p < 0.05, indicating a significant difference between pre- and post-education. It can be concluded that education delivered through lecture and demonstration methods is effective in enhancing pregnant women’s understanding of Birth Ball use.